2007
DOI: 10.1074/jbc.m702229200
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Acid-sensing Ion Channel (ASIC) 4, Characterization of Homo- and Heteromeric Channels, and Identification of Regions Important for Activation by H+

Abstract: There are four genes for acid-sensing ion channels (ASICs) in the genome of mammalian species. Whereas ASIC1 to ASIC3 form functional H ؉ -gated Na ؉ channels, ASIC4 is not gated by H ؉ , and its function is unknown. Zebrafish has two ASIC4 paralogs: zASIC4.1 and zASIC4.2. Whereas zASIC4.1 is gated by extracellular H ؉ , zASIC4.2 is not. This differential response to H ؉ makes zASIC4 paralogs a good model to study the properties of this ion channel. In this study, we found that surface expression of homomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…The mechanism by which VHA activity promotes Na + uptake is not yet known; however, two alternatives may exist: firstly, VHA charges the apical membrane potential thereby increasing the electrochemical gradient for Na + to enter in the cell through ASIC, and secondly, VHA provides a gating signal to ASIC by acidification of the boundary layer, since ASICs are gated by extracellular H + ions that activate several amino acid residues located in different extracellular domains (Bonifacio et al, 2014;Paukert et al, 2008). One complicating factor is that ASIC4.2 has been demonstrated to be insensitive to extracellular H + (Chen et al, 2007). However, there is evidence that ASICs assemble into homoor heteromeric trimers (Jasti et al, 2007), therefore it is possible that ASIC4.2 forms a channel with other ASIC subunits that show extracellular H + gating.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which VHA activity promotes Na + uptake is not yet known; however, two alternatives may exist: firstly, VHA charges the apical membrane potential thereby increasing the electrochemical gradient for Na + to enter in the cell through ASIC, and secondly, VHA provides a gating signal to ASIC by acidification of the boundary layer, since ASICs are gated by extracellular H + ions that activate several amino acid residues located in different extracellular domains (Bonifacio et al, 2014;Paukert et al, 2008). One complicating factor is that ASIC4.2 has been demonstrated to be insensitive to extracellular H + (Chen et al, 2007). However, there is evidence that ASICs assemble into homoor heteromeric trimers (Jasti et al, 2007), therefore it is possible that ASIC4.2 forms a channel with other ASIC subunits that show extracellular H + gating.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that, similar to ENaCs, functional ASICs are trimers (20), although their configuration has not been resolved. It has been demonstrated that, with a few exceptions, ASICs function as homomers (forming channels of identical subunits) or heteromers (forming channels with other ASIC subunits) (4,23). ASICs have been characterized by using oocyte expression in zebrafish (4,35) and dogfish shark (ASIC1b only) (42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that, with a few exceptions, ASICs function as homomers (forming channels of identical subunits) or heteromers (forming channels with other ASIC subunits) (4,23). ASICs have been characterized by using oocyte expression in zebrafish (4,35) and dogfish shark (ASIC1b only) (42). It has been found that coexpression of zASIC4.1 with zASIC1.3 in Xenopus oocytes increased the current amplitude and abundance (ϳ15-fold) of the channel at the cell surface, indicating that these two ASIC subunits form a functional channel (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using chimeras composed of proton-insensitive and proton-sensitive ASICs suggest that specific residues within the wrist domain of ASICs are required for proton-dependent activation (35)(36)(37). Channels that are unresponsive to protons are produced when these residues are mutated, and because some of these residues can be titrated by protons, it has been suggested that they represent the proton-binding site(s).…”
Section: Discussionmentioning
confidence: 99%